100 years of STIs in the UK: a review of national surveillance data. (13th April 2018) - Mohammed, Hamish; Blomquist, Paula; Ogaz, Dana; Duffell, Stephen; Furegato, Martina; Checchi, Marta; Irvine, Neil; Wallace, Lesley A; Thomas, Daniel Rhys; Nardone, Anthony; Dunbar, J Kevin; Hughes, Gwenda
Abstract : Objectives: The 1916 Royal Commission on Venereal Diseases was established in response to epidemics of syphilis and gonorrhoea in the UK. In the 100 years since the Venereal Diseases Act (1917), the UK has experienced substantial scientific, economic and demographic changes. We describe historical and recent trends in STIs in the UK. Methods: We analysed surveillance data derived from STI clinics' statistical returns from 1917 to 2016. Results: Since 1918, gonorrhoea and syphilis diagnoses have fluctuated, reflecting social, economic and technological trends. Following spikes after World Wars I and II, rates declined before re-emerging during the 1960s. At that time, syphilis was more common in men, suggestive of transmission within the men who have sex with men (MSM) population. Behaviour change following the emergence of HIV/AIDS in the 1980s is thought to have facilitated a precipitous decline in diagnoses of both STIs in the mid-1980s. Since the early 2000s, gonorrhoea and syphilis have re-emerged as major public health concerns due to increased transmission among MSM and the spread of antimicrobial-resistant gonorrhoea. Chlamydia and genital warts are now the most commonly diagnosed STIs in the UK and have been the focus of public health interventions, including the national human papillomavirus vaccination programme, which has led to substantial declines in genital warts in young people, and the National Chlamydia Screening Programme in England. Since the 1980s, MSM, black ethnic minorities and young people have experienced the highest STI rates. Conclusion: Although diagnoses have fluctuated over the last century, STIs continue to be an important public health concern, often affecting more marginalised groups in society. Prevention must remain a public health priority and, as we enter a new era of sexual healthcare provision including online services, priority must be placed on maintaining prompt access for those at greatest risk of STIs.